The Effects of Social and Cultural Factors on Child Poly-victimization in Hong Kong - Chen, Qiqi (Journal of interpersonal violence, 2022)
Study Questions Child victimization is a major public health concern across the globe. Many previous studies have focused on separate categories of child victimization and health correlates, paying less attention to children affected by multiple forms of violence. Studies encompassing families? residential mobility and social support in the context of child poly-victimization are limited. This study examines the prevalence of child poly-victimization in Hong Kong and the associations between family structure, residential mobility, social support, and child poly-victimization. Subjects and Methods The analysis employed data from a cross-sectional, school-based survey in Hong Kong. A two-stage stratified sampling procedure was employed to maximize the representativeness of the sample. All children born in Hong Kong and receiving education in the sampled schools were included as eligible participants. A total of 5,567 children and their caregivers from 107 schools (kindergartens, primary schools, and secondary schools among 18 districts in Hong Kong) were randomly recruited in the study. Findings A total of 32.2% of the children experienced one-to-three types of victimization and 23.1% reported experiencing four or more types of victimization in the preceding year. Child victimization and its various aspects were negatively associated with family support, positively correlated with the number of times the child had moved house, and the number of siblings at home. The strongest association appeared to be between child maltreatment and family, while a relatively weaker but still significant connection was found between peer and sibling victimization and family support. Major Implications Successful family functioning and social stability are key to protecting children from victimization. This study provides insights into the importance of supporting families as a whole in preventing child poly-victimization. It also highlights family structure and social support in reducing the negative impacts of child victimization.